(untitled) - Women and action and resource initiative (WARI) (Bangkok, 2002)
This document consists of the reports and meeting documents from the Training course on Gender and development in SE Asia (Indochina), Feb, 18th - 28th, 2002 in Thailand. The training course aimed to increase gender related conceptual and analytical capacity of participants (both men and women) ; to situate and link global debates on gender to local Asian contexts and needs ; and to promote interaction and exchange among gender development workers, students and teachers in SE Asia and the great Mekong sub-region.
Keywords: Women in public life,Phụ nữ